Penyelesaian Sengketa Ekonomi Syariah dalam Transaksi Jual Beli Ikan di Desa Tanjung Pesisir Kabupaten Sampang: Pendekatan Sosio-Religius - Safira Adibatul Faruq (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to examine how to resolve Sharia-compliant economic issues in fish trading in Tanjung Pesisir Village, Sampang Regency, using an approach that combines social and religious aspects. This village is a coastal area heavily dependent on the fishing industry, where fish trading is conducted traditionally without written contracts and is based on trust between business actors. However, economic problems often arise, such as price disputes, quality differences, late payments, and lending practices that disadvantage fishermen.The method used in this research is a qualitative approach using case study techniques and socio-religious analysis to determine how social and religious values ​​influence community conflict resolution. Findings indicate that the community prefers to resolve problems through family deliberations with the assistance of religious figures such as kiai (Islamic scholars) or ustaz (Islamic religious teachers). This informal resolution method is considered more effective in maintaining social harmony and is in accordance with Sharia principles, although it does not provide definitive legal guarantees. Therefore, efforts are needed to align local approaches with the Sharia-compliant economic legal system through community education and the establishment of community-based mediation institutions focused on the principles of justice and sustainability.